KEANEKARAGAMAN JENIS BURUNG DIURNAL DI KAWASAN HUTAN KOTA GUNUNG SARI KOTA SINGKAWANG - Awaluddin, Wisnu; Said, Syafruddin; anto, Eri (Universitas Tanjungpura, 2014)
Forest City Gunung Sari has a potential that needs to be extracted and can be used for example to value the beauty that can be used as a tourist attraction. Bird was instrumental in building a tourist park because of its beauty is the value of voice and other fur. The beauty of birds of all he had to give a pleasure in itself. Based on the results of observations show that of the three habitats in the path of observation, obtained the number of diurnal birds have been found in the study site 18 species, classified into 13 families, namely : (Accipitridae), (Columbidae), (Aegithinidae), (Nectariniidae), (Dicaeidae), (Hirundinidae), (Estrildidae), (Psittaculidae), (Timaliidae), (Cisticolidae), (Passeridae), (Pycnonotidae), (Picidae). Primer forest habitats found in 13 species of diurnal birds, 12 species of secondary forest habitats and 9 species around the estate. From the calculation, the highest dominance index contained in the habitat surrounding forest plantations morning time C=0.1613, day time C=0.1458, and the afternoon time C=0.1264. While the species diversity index was highest in primary forest habitat value morning time =1.0531, day time =1.0397, =0.0260 late afternoon and secondary forest habitats have a high diversity index values ​​in the morning with value of =1.0287. Habitat differences provide a clear influence of the dominant species, in which the dominance of this species is the opposite of diversity. Diversity of small species produce mastery of habitats, so that the dominance of the species will be spread more evenly due to the small number of species that might be the number of individuals to live and breed better. Keywords: Diversity of species , diurnal bird , forest city Gunung Sari.